2007
DOI: 10.1016/j.mimet.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Commercial ampholytes used for isoelectric focusing may interfere with bioactivity based purification of antimicrobial peptides

Abstract: BioRad's Rotofor ® system has been frequently used for the purification of proteins and smaller peptides such as bacteriocins. In this study, we report that some commercially available ampholytes used with the Rotofor ® isoelectric focusing system possess antimicrobial activity, which may interfere with the purification of bacteriocins and bacteriocin-like substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The lactosporin preparation used in the mode of action study was active against M. lutues (indicator strain) and G. vaginalis when tested in a well diffusion assay as reported in our previous publication (Riazi et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The lactosporin preparation used in the mode of action study was active against M. lutues (indicator strain) and G. vaginalis when tested in a well diffusion assay as reported in our previous publication (Riazi et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…; Riazi et al . ). G. vaginalis ATCC 14018 was grown on a selective human blood Tween bilayer agar medium at 37°C, anaerobically.…”
Section: Methodsmentioning
confidence: 97%
“…The zones of inhibition of tested samples from fractions 18, 19 and 20 were large (5, 7 and 12 mm respectively), without a clearly‐defined edge; in contrast, the zone of inhibition of fraction 1 was small with a well‐defined edge. Further experiments showed that the antimicrobial activity seen in fractions 18–20 was due to the ampholyte used in the Rotofor system (Riazi et al. 2007), and that fraction 1 is the active fraction of the LP.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of each fraction was tested against Micrococcus luteus in a well diffusion assay. Bars with asterisks indicate fractions with antimicrobial activity due to the activity of the ampholyte used in isoelectric focusing(Riazi et al 2007). Native-PAGE visualization of 5· and 10· concentrated lactosporin preparation.…”
mentioning
confidence: 99%
“…The IEF technique requires the generation of background pH gradient and usually, the synthetic carrier ampholytes are used for this purpose . However, they can constitute the issues such as their low compatibility with subsequent analysis by MS , their interferences with sample biological activity , and high analysis cost, especially in continuous flow systems. Although four potential modes of IEF in nonamphoteric buffers were discussed in 1985 (stack of free bases and acids, chemically bonded immobilized pH gradients, physically bonded pH gradients, and steady‐state rheoelectrolysis), the authors concluded that only immobilized pH gradients have proved to be reliable technique easily transplantable in any laboratory, since some of the other modes were not based on the explicit models and they might fail.…”
Section: Introductionmentioning
confidence: 99%